Development of variable intake system for sparkignition engine - Muhammad Hafizuddin, Salim (2012)
This project is to study about the development of variable intake manifold for sparkignition engine. Variable intake manifold is one of the methods in optimizing the performance of an engine. Some of manufacture have great interest on this system such as Volkswagen and Volvo companies. Further research was held by those companies. Each of them has different in design in order to race in technology of engine optimizing. This experiment was conducted by using flow bench that test on the flow rate of the new design intake manifold that has been fabricated. The test is on the intake manifold that is used by the 1600cc engine. Two intake manifolds were tested in this experiment, the Proton Waja intake manifold and the custom intake manifold that has been fabricated. The result found that the length of runner does affect the flow rate that produced by the intake manifold. The long runner will give better flow rate on the earlier phase of engine speed while the shorter runner will give better flow rate on the top end of engine speed. That is the reason why the variable intake manifold is better intake manifold compared to the standard intake manifold because it can be switch for the suitable length of runner depends on the engine speed condition.